Rol de interleuquina-6 en artritis reumatoide: nuevos conceptos - Soto S., Lilian; Catalán M., Diego; Sabugo S., Francisca; wurmann k., Pamela; Aguillón G., Juan Carlos (Revista Hospital Clínico Universidad de Chile, 2011)
Rheumatoid arthritis (RA) is a chronic inflammatory disease of unknown etiology that involves complex and not completely elucidated mechanisms. In the recent years, the development of targeted therapies has given new insights into the nature of immunologic interactions involved in its pathogenesis. Until recently, the RA was thought to be predominantly a Th1 disease. New evidence established the preponderant role of the Th17 axis, of which IL-17 and IL-23 are major components. IL-6 has an important role in the differentiation of the Th17 and T regulatory (Treg) lymphocytes. Herein, we review current evidence regarding the role of cytokines in the pathogenesis of RA, especially in the differentiation of Th17 and Treg systems, as well as the deleterious effects of IL-6 and the molecular and clinical consequences of its blockade.